Application Of Web Engineering Methods In Designing A Building Rental Information System In Kemuning Building Bekasi - Siti Nurajizah; Wicaksono, Bambang Rizki (Institute of Computer Science (IOCS), 2020)
The building is a place to hold an event with a large number of visitors. The use of the building in holding an event makes it easier for event organizers in the process of implementing the event. The current building rental system at the Kemuning building hall takes a long time in the process of renting the building. The search for information and the process of listing the status of building leasing still uses a manual system, which is recorded in a rental book. This can make the building rental system unstructured and poorly controlled. An information system can make it easier for tenants in the rental process for the yellow building. The building rental information system application uses the web engineering method which aims to build an integrated information system that can engineer the web with several technical requirements and identify information. The resulting information system is a building rental website that can minimize errors made by officers in registering tenants, data building rental recapitulation, avoiding data manipulation and being a distinct advantage for managers who prioritize technological advances by using the system through website-based database applications. The features on this website include a list of packages offered, the ease of making building rental reservations and making the payment process easier. This building rental information system can provide convenience for consumers and officers in the process of renting a building and managing data on the rental of the Kemuning building.